2020
DOI: 10.21608/ejap.2020.100851
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Perspectives of Microalgae-Aquaculture in Egypt, Case Study: Simaf-Prototype-Project

Abstract: Aquaculture is a global industry that supplies essential food to a growing world population and contributes more than 77% of the total Egyptian national fish production. Despite Egypt has a great potential in marine aquaculture, more than 95% of Egyptian aquaculture production is categorized as fresh water aquaculture. Until now, Egypt has no real marine aquaculture and this is attributed to many obstacles. One of these obstacles is the quality and quantity of microalgae in the marine hatcheries. Another obsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The minimum values may be related to increases in plankton biomass. The high phytoplankton population in water bodies utilizes a high content of ammonium ions in preference to other inorganic nitrogen [49]. Our results agree with Okbah and Hussien [25], who showed that in the regional variations of NH 4 , the minimum mean concentration was 3.70 µmol L −1 .…”
Section: Water Characteristics and Physicochemical Parameterssupporting
confidence: 91%
“…The minimum values may be related to increases in plankton biomass. The high phytoplankton population in water bodies utilizes a high content of ammonium ions in preference to other inorganic nitrogen [49]. Our results agree with Okbah and Hussien [25], who showed that in the regional variations of NH 4 , the minimum mean concentration was 3.70 µmol L −1 .…”
Section: Water Characteristics and Physicochemical Parameterssupporting
confidence: 91%
“…As reported previously, seaweed liquid fertilizers could increase chlorophyll content [20], increase total yield [4], and improve the root system [21]. In conjunction with its rapid and easy handling process, the applicability of seaweed extract foliar spraying has been studied [22], with a focus on stimulating growth and increasing the productivity of some important vegetable crops, such as cucumber [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…At present, biodiesel's production cost is from 1.5 to 3-fold more than fossil diesel due to the high cost of raw feedstocks and unavailability of oil crops utilized for human food consumption [2]. Algal biomass are considered an attractive natural source of bioactive materials that can be utilized in several applications such as food industry [3], pharmaceuticals [4], cosmetics [5], biogas and biodiesel [6,7], antimicrobial and antioxidant activities [3,8], aquaculture [9][10][11][12], biofertilizers and bioremediation [13][14][15][16]. Therefore, the screening of native microalgae species is necessary to realize a potent algal database with effective commercial biotechnological applications [3,17].…”
Section: Introductionmentioning
confidence: 99%